Delivering Low Tidal Volume With Anesthesia and ICU Ventilators in a Neonatal Lung Model. - Medeiros, Kyle J.; Morais, Caio A.; Winterton, Dario; Rub, David M.; De Santis Santiago, Roberta; Shekhar, Nitika; Chipman, Daniel; Monaghan, Thomas T.; Bittner, Edward A.; Carroll, Ryan; Berra, Lorenzo (Respiratory Care, 2023)
BACKGROUND: Mechanical ventilation of the neonate requires ventilators than can deliver precise and accurate tidal volume (VT) and PEEP to avoid lung injury. Due to small neonatal VT and the disproportionate effect of endotracheal tube leak in these patients, accomplishing precise and accurate VT delivery is difficult. Whereas neonatal ICU ventilators are validated in this population, thorough studies testing the performance of anesthesia ventilators in delivering small VT in neonates are lacking. METHODS: Three anesthesia ventilators, Dräger Apollo, GE Avance, and Getinge Flow-i; and 2 ICU ventilators, Medtronic PB980 and Nihon Kohden NKV-550, were tested under volume control mode at VT of 5, 20, 40, and 60 mL. Three combinations of lung compliance and airway resistance were tested using a Servo ASL 5000 lung simulator. RESULTS: In a scenario without leak, the measured VT was greater than the set VT by > 10% in the Apollo (21.0% [18.8-26.0]); measured VT was less than the set VT by > 10% in the Flow-i (-19% [-20.8 to -18.7]). The Avance, PB980, and NKV-550 presented a volume error < 10% (-9.50% [-10.8 to -4.4], -5.8% [-11.8 to -3.5], and 5.4% [-4.5 to 18.9], respectively). Considering all combinations of set VT, leaks, and respiratory mechanics, none of the anesthesia ventilators were able to deliver a median measured VT within a 10% error. The bias between measured VT and set VT varied widely among ventilators (from 4.27 mL to -10.59 mL). Additionally, in the Apollo ventilator, PEEP was underdelivered with the largest leak value. CONCLUSIONS: Our results suggest that in comparison with the 2 neonatal ICU ventilators tested, the anesthesia ventilators did not greatly differ in terms of VT delivery in the presence of a gas leak.